Schooling Experiences of Tamang Girls in Nepal - Shyangtan, Sharmila (Journal of Education and Research, 2020)
School education is the foundation for continuing education and attainment of basic skills and knowledge. Despite the international promises such as Education for All, Universal Primary Education, and national provision of school education as free and compulsory in Nepal, most of the marginalised people could not complete their school education. Among them, girls from the Tamang community are still confronting insurmountable challenges in accessing and undergoing schooling experience in Nepal. This paper argues that the schooling process of the Tamang girls is influenced by the embedded characteristics of cultural setting and their subjectivities through their stories. Using narrative inquiry as a research method for the study, this paper explored that schooling is shaped by the complex and dynamic role of embedded identities, power, and historicity of the community and people. I present how the Tamang girls experience their school education and how it has been the foundation for their higher education journey as well as identities formation. The paper concludes that identities of Tamang girls in school are multiple, intersubjective, and contextual, which are less recognised in modern schooling.